Additions to the revision of Dima Charpentier, 1825 (Coleoptera: Elateridae: Dimini) in the Balkan Peninsula, with the descriptions of five new species - Mertlik, Josef; Németh, Tamás; Kundrata, Robin (Zootaxa, 2018)
Complementary revisionary information is provided for the click-beetle genus Dima Charpentier, 1825 in the Balkan Peninsula. Five species are described as new for science: Dima bialookii sp. nov. (Greece), D. blazeji sp. nov. (Albania), D. gazureki sp. nov. (Albania), D. timfristosensis sp. nov. (Greece), and D. tomorrensis sp. nov. (Albania). The male of D. hirtipennis Platia, 2011 is described for the first time. Dima etoliensis Platia, 2012 syn. nov. is a subjective junior synonym of D. evritaniensis Schimmel & Platia, 2008. New specimens and distributional data are reported for D. assingi Schimmel & Platia, 2008, D. dalmatina Küster, 1844, D. elateroides Charpentier, 1825, D. evritaniensis, D. florinensis Platia, 2012, D. hirtipennis, D. hladilorum Schimmel, 1987, D. lebenbaueri Schimmel & Platia, 2008, D. macedonica Schimmel, 1993, D. marvani Mertlik & Dusanek, 2006, D. neumanni Platia, 2013, D. olympica Meschnigg, 1934, D. parnonensis Schimmel & Platia, 2008, D. pecoudi Fleutiaux, 1944, D. pelikani Mertlik, Németh & Kundrata, 2017, D. pelionensis Mertlik, Németh & Kundrata, 2017, D. vailatii Schimmel & Platia, 2008, and Dima sp. cf. orientalis Mertlik, Németh & Kundrata, 2017. Morphological variability in D. hladilorum is discussed. Figures of habitus and main diagnostic features are provided for all new species, D. evritaniensis from Nerosirtis surroundings in Panetolikó Mts. (i.e., type locality of D. etoliensis syn. nov.), and for the male of D. hirtipennis. Additionally, we update the distribution maps for the genus Dima in the Balkans based on the new findings. Currently, 37 described species of Dima are known from the Balkan Peninsula. We discuss the morphological diagnostic characters for Dima species and call for the molecular phylogenetic study for this group.